Quantifying genotypic variation and the effect of phosphorus on root system architecture, P use efficiency, yield and physiological seed quality of Cowpea Genotypes - Mohammed, Kotochi Clement (University of Cape Coast, 2020)
Cowpea (Vigna unguiculata (L) Walp) plays an important role in the livelihoods of several millions of people in the world. Despite its importance, poor soil fertility often limits the yield of cowpea in many areas, especially in the tropics, where the prevalently old and highly weathered soils have a low bioavailability of soil phosphorus (P). Plants have evolved adaptive mechanisms to low-P soils. The mechanisms include modification of root system architecture (RSA). Breeding for cowpea genotypes which use soil P efficiently and have superior RSA traits will enhance yield and ultimately promote food security and livelihoods of the millions of people who depend on the crop. The aim of this study was to evaluate genotypic variation and the effect of external P concentration ([P]ext) on RSA, yield, and physiological seed quality among 20 cowpea genotypes under field conditions. The study also evaluated the variation in P use efficiency (PUE) parameters including agronomic P use efficiency (APE), P uptake efficiency (PUpE), and P efficiency ratio (PER). An 8 × 8 Alpha lattice design was used to screen cowpea genotypes in two seasons under 3 [P]ext, namely 0, 10 and 45 kg P/ha. The results showed that there were significant (P<0.05) genotypic variations among cowpea genotypes in almost all the traits examined. For example, the stem diameter, hypocotyl root length and basal root length of genotypes Sunshine and WC35B*NE50 were greater compared to that of genotype Agyenkwa and NE15*WC35B. [P]ext significantly affected many traits, including yield, root growth angle, root length, tissue P concentration and germination percentage. There was increasing trend in hypocotyl root length, tissue P concentration, germination percentage and yield with increasing [P]ext. On the other hand, increasing [P]ext resulted in a significant (P<0.01) reduction in PER and PUtE. Some genotypes, including Secow3B, NE50, IT91 and WC35B*NE50 were categorized as P-efficient genotypes because they developed higher biomass weight and root length under low [P]ext. The shoot and root concentrations of P were significantly (P<0.01) affected by genotypes and P fertilizer application rate. The highest yielding genotypes took up more P than the low yielding ones. Differential yield response of cowpea in the field to [P]ext was observed. Grain yield increased with P application rate up to 45kg/ha. Days to flowering, number of branches, pod length etc. among genotypes were significantly high at 45 kgP/ha. Genotypes with longer root length such as Secow5T, WC36 had high tissue P concentration and yield confirming the role of the root system in the uptake of immobile P. The results have important implications for breeding and selection of cowpea genotypes that are adapted to a range of fertility levels. The results could be used to select for cowpea genotypes with superior RSA traits and improved PUE for use on P-poor soils and provide potential germplasm for breeding new cowpea cultivars better adapted to P-poor soils in Ghana.
xxi, 172p:,ill.
Keywords: Seed quality; Genotypic variation; Phosphorus use efficiency; Root system architecture; Cowpea (Vigna unguiculata)